HUBUNGAN TINGKAT PENGETAHUAN DAN SIKAP IBU TERHADAP PERILAKU PENCEGAHAN COVID-19 PADA ANAK BALITA DI UPTD PUSKESMAS KECAMATAN LIMO KOTA DEPOK - Laula Sekar Tadji, (2023)
COVID-19 is an infectious virus caused by SARS-CoV-2 which attacks the respiratory system and transmits from human to human through coughing or saliva splashes. The spread is so fast and it is very easy to infect toddlers because of the low level of immune system. Mother's role is very important in stopping the spread of COVID-19 by carrying out various prevention efforts. The purpose of this study was to determine the relationship between mothers level of knowledge and their attitudes toward COVID-19 preventive behaviors.in toddlers at the Integrated Regional Technical Implementation Unit (UPTD) of the Limo District Health Center, Depok City. The methodology of this study is a quantitative analysis with a cross-sectional design. The sampling technique used consecutive sampling with a total sample of 42 mothers of children under five who had confirmed COVID-19 at the Limo District Health Center UPTD. Data analysis in this study is univariate analysis and bivariate data analysis with chi-square. The results of the study of the 42 samples provided balanced low and high knowledge, namely 21 mothers (50.0%), 26 mothers (61.9%) had a positive attitude, and 27 mothers (64.3%) had COVID-19 prevention behavior by good category. The results showed no significant correlation between awareness and COVID-19 preventive behavior. There was a significant correlation between awareness and COVID-19 preventive behavior. Therefore, it is recommended that all mothers get a better understanding and attitude towards the proper COVID-19 prevention behavior for toddlers.